Excavations and archaeological studies in the district of Yanahuanca, Pasco region, Peru - Bueno Mendoza, Alberto (2018)
The ancient Yarush Culture (Yaro in Spanish) is beginning to be discovered for Andean archeology. The archaeological investigations were carried out by the Pasco Regional Government Agreement / National University of San Marcos, 2007-2010. The works were executed in the outskirts of the present towns of Astobamba: archaeological site of Yarushpampa; Rocco village: Goñicutac archaeological site; village of Vilcabamba: archaeological site of Gorish and current village of Huarautambo: archaeological site of Guarautambo. The article proposes the debate about the origins of the Yarush in the Huayhuash m ountain range and its first settlement at the site of Yarushpampa; In addition, the excavations of the Tawantinsuyu site of Guarautambo are reported on the left bank of the river of the same name.